Evaluation of Medication Errors in Preparation and Administration of Intravenous Medicines in Intensive Care Units in Imam Reza and Shohada Hospitals in Tabriz - Hadi Hamishehkar; Simin Mashayekhi; Mohammadreza Gaffari; Mehrdad Shahidi (Research Center for Rational Use of Drugs (RCRUD), 2022)
Background: Studies have shown that medication errors and adverse drug reactions are among the main causes of adverse events in hospitals leading to disability and death. Errors occur in the process of drug prescribing, dispensing, and administration. errors are most often made on the patient care units with various risk factors. The aim of the study was to evaluate medication errors in preparation and administration of intravenous medications in two Intensive Care Units of two university hospitals in Tabriz.Methods: An observational and single-blinded study was carried out in the pulmonary ICU of Imam Reza hospital and the ICU of Shohada hospital using general and mono-drug checklists of error-prone situations. 14 different error categories were studied.Results: Total of 367 administrations for 26 different drugs were observed.  among 4558 opportunities for errors, 640 errors were identified. Error rate of 15.99 % and 10.96 % were reported in Imam Reza and Shohada hospital, respectively. Wrong rate error and controls during administration had the highest rate of errors in Imam Reza and Shohada hospitals, respectively. Streptokinase in Imam Reza hospital and ceftazidime in Shohada hospital were the drugs with highest error rate. Midnight and 10 PM administration rounds had the highest error rate in Imam Reza and Shohada hospitals, respectively. Error rate in Imam Reza hospital was significantly higher.Conclusion: It is concluded that medication errors occur in all stages like preparation and administration mostly related to rate of administration and controls needed while administration; Strict controlling, training programs, and presence of clinical pharmacists are highly recommended.